Convention attendance and gaming volume in South Korean casinos. Issue 1 (7th March 2016) - Malek, Kristin; Kim, Jungsun (Sunny)
Abstract : Purpose: – The purpose of this paper is to advance a theoretical model by estimating the effects of convention attendance on gaming volume (both monthly coin-in and table game drop). Design/methodology/approach: – Performance monthly data from two casinos in South Korea are used to test the research model. Specifically, time series regression modeling was performed on the data with the dependent variables including coin-in and table drop and the independent variables including convention attendance and hotel occupancy. Findings: – The hotel occupancy variable was found to significantly increase slot coin-in at a rate of 113, 603, 912 KRW (approximately US$93, 500) per month at Casino A. Interestingly, this variable had a significant negative relationship with coin-in per month at Casino B. Meanwhile, the hotel occupancy variable failed to produce any significant effect in the table drop model at both casinos. The convention attendance variable also had no significant effect on both coin-in and table drop at both casinos. Originality/value: – This research represents the first attempt to empirically examine the effects of convention attendance on gaming revenues in Asian markets.